Faktor yang Mempengaruhi Kecanduan Gadget terhadap Perilaku Remaja - Rezky Graha Pratiwi; Rosyidah Umpu Malwa (Jurnal Ilmiah Psyche, 2021)
This study aims to determine how big the influence of gadget addiction on the behavior of class VIII students at Mts Ma'Ariful Ulum Talang Keramat Banyuasin. The hypothesis proposed in this study is that there is an influence between gadget addiction on the behavior of class VIII students at Mts Ma'Ariful Ulum Talang Keramat Banyuasin. The population in this study was all students of class VIII as many as 110 students, the subjects of this study were 55 students and random sampling technique. Collecting data using addiction and behavior scales, data processing techniques using SPSS. The results of the regression analysis showed R square = 0.277, F = 20.286 and p = 0.000 (p <0.05) with N = 55 and an rtable of 0.266. This shows that addiction has an influence on behavior. Thus, the hypothesis of this study can be accepted that the contribution of addiction to behavior is 27.7%.